2019
DOI: 10.1088/1757-899x/687/6/066061
|View full text |Cite
|
Sign up to set email alerts
|

Use of municipal vegetative waste as raw material for sorbent production

Abstract: The most important direction of waste management is to reduce the resulting environmental impact. One of the promising ways of waste recycling is their use as a raw material for the production of sorbents. The paper presents the results of studies on the possibility of using ChL250, i.e. modified municipal vegetative waste for cleaning the storm runoff of service stations from petroleum products and associated pollutants. It was found that the sorption capacity of the material for petroleum prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In this context, studies have shown that farmers gain high income from biogas production and worm fertilization [8]. On the other hand, considering the dependence on fossil fuels, the fact that fossil fuels are exhaustible and pose an environmental threat reveals results that support the idea of using organic wastes as energy and raw materials [9][10]. If organic wastes are not utilized, their storage poses a problem.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies have shown that farmers gain high income from biogas production and worm fertilization [8]. On the other hand, considering the dependence on fossil fuels, the fact that fossil fuels are exhaustible and pose an environmental threat reveals results that support the idea of using organic wastes as energy and raw materials [9][10]. If organic wastes are not utilized, their storage poses a problem.…”
Section: Introductionmentioning
confidence: 99%